Insurance against ice risks at Sea - Armstrong, Terence (Polar Record, 1957)
Normal insurance of hulls is not valid when vessels sail into certain waters where additional risks are incurred. These areas are exactly defined in a document produced by the Institute of London Underwriters known as the Institute Warranties , reproduced as Appendix 1. If a ship is required to sail in any of these waters, for instance Hudson Bay, or the Baltic Sea in winter time, suspension of the Warranty must be obtained from the underwriters by payment of additional premium to cover the additional risks involved. The nature of these risks is not specified, but clearly ice is a principal one in these two areas, and in some of the other areas.